A Repeated-measures Case Series of Physiological Responses to a Transoceanic Rowing Race - Keohane, David M.; Woods, Trevor; McCarthy, Yvonne; O'Connor, Patrick; Underwood, Sean; Molloy, Michael G. (International Journal of Sports Medicine, 2019)
This repeated-measures case series describes the changes in cardiorespiratory fitness, body composition and systemic inflammation in 4 well-trained athletes pre- and post-completion of an unsupported transatlantic rowing race. The acute effects of endurance exercise have been well described previously, but the enduring consequences of ultra-endurance on the cardiorespiratory, metabolic and immune systems are largely unknown. This study explores these physiological adaptations following 2 weeks of recovery. Cardiorespiratory fitness testing, body composition analysis, and blood sampling for inflammatory cytokines were recorded immediately before race departure and repeated 14 days following race completion. Mean VO2max (ml/kg/min) was similar pre- (48.2±2.8) and post-race (46.7±1.5). Heart rate responses were equivalent at incremental workloads. Mean blood lactate (mmol/L) was higher at low to moderate power outputs and lower at maximal effort (14.6±1.85 vs. 13.1±2.5). Percentage body fat (17.7 ± 7.9 vs. 16.2±7.4) was analogous to pre-race analysis. Low-grade inflammation persisted, indicated by an increase in IL-1β (69%), IL-8 (10%), TNF-α (8%), IL-6 (5.4%), and C-reactive protein (22.4%). VO2max and heart rate responses were similar pre- and post-race, but sub-maximal efficiency measures of cardiorespiratory fitness were consistent with persistent fatigue. Body composition had returned to baseline but low-grade systemic inflammation persisted. Persistent pro-inflammatory cytokinaemia is known to exert deleterious consequences on immune, metabolic, and psychological function. Adequate recovery is necessary to re-establish inflammatory homeostasis, and the results of this study may inform these decisions.
Keywords: endurance; rowing; recovery; exercise physiology; inflammation